Endoscopic Skull Base Surgery Protocol From the Frontlines: Transnasal Surgery During the COVID‐19 Pandemic. (26th May 2020) - Spock, Todd; Kessler, Remi; Lerner, David; Filip, Peter; Del Signore, Anthony; Colley, Patrick; Morgenstern, Peter; Schaberg, Madeleine; Bederson, Joshua; Govindaraj, Satish; Iloreta, Alfred Marc; Shrivastava, Raj
Abstract : Objective: The coronavirus disease 2019 (COVID‐19) pandemic disrupted the standard management paradigms for care of patients with sinus and skull base presentations due to concern for patient and health care provider safety, given the high aerosol‐generating potential of endonasal procedures. Data Sources: We reviewed the relevant literature complied from available sources, including PubMed, Google Scholar, and otolaryngology journals providing electronic manuscripts ahead of indexing or publication. Review Methods: Incorporating available evidence and the projected infection control and resource limitations at our institution, we collectively authored a dynamic set of protocols guiding (1) case stratification, (2) preoperative assessment, (3) operative setup, and (4) postoperative care of patients with sinus or skull base presentations. Due to the rapidly evolving nature of COVID‐19 publications, lack of rigorous data, and urgent necessity of standardized protocols, strict inclusion and exclusion criteria were not employed. Conclusions: As scarce hospital resources are diverted to COVID‐19 care and staff are redeployed to forward‐facing roles, endonasal procedures have largely ceased, leaving patients with ongoing sinonasal and skull base complaints untreated. Skull base teams now weigh the urgency of surgery in this population with the regional availability of resources. Implications for Practice: The COVID‐19 pandemic will have an enduring and unpredictable impact on hospital operations and surgical skull base practices and will require a dynamic set of management protocols responsive to new evidence and changing resources. In the current resource‐limited environment, clinicians may utilize these protocols to assist with stratifying patients by acuity, performing preoperative assessment, and guiding peri‐ and postoperative care.